2021
DOI: 10.3390/cryst11030250
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrodynamics, Li+ Addition and Transformation Kinetics on the Formation of Plate-Like {001} Calcite Crystals

Abstract: Plate-like calcite crystals with expressed unstable {001} planes are interesting research model for investigations of interfacial interactions of different additive molecules, but also the crystal growth mechanisms. The aim of this study is to reproducibly prepare a significant amount of well-defined plate-like calcite crystals and to investigate the critical experimental parameters. Thus, in precipitation system c(NaHCO3) = c(CaCl2) = 0.1 mol dm−3, the influence of hydrodynamic parameters (mode of mixing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In our previous investigation [27] it was shown that pH and supersaturation are important and interconnected parameters that could influence the morphology, polymorphic composition and/or kinetics of CaCO 3 precipitation in precipitation systems with different chemical complexities. Apart from thermodynamic parameters, our investigations also showed that hydrodynamics has significant influence on calcium carbonate precipitation processes and on properties of CaCO 3 precipitated [29].…”
Section: Introductionmentioning
confidence: 68%
“…In our previous investigation [27] it was shown that pH and supersaturation are important and interconnected parameters that could influence the morphology, polymorphic composition and/or kinetics of CaCO 3 precipitation in precipitation systems with different chemical complexities. Apart from thermodynamic parameters, our investigations also showed that hydrodynamics has significant influence on calcium carbonate precipitation processes and on properties of CaCO 3 precipitated [29].…”
Section: Introductionmentioning
confidence: 68%
“…It has been studied that the transformation kinetics of vaterite to calcite extend with increasing Li + concentration at ultrasonic irradiation condition. [ 18 ] Besides, atomistic simulation [ 24 ] and in situ AFM observations [ 25 ] showed that Li + could stabilize the energetically unfavorable (001) face by the site‐selective interaction to reduce its surface energy. This behavior will be expressed in the predominant growth of the uncovered faces and modification of the equilibrium calcite morphologies.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we investigated the role of alcoholic ─OH groups and carboxy groups of low molecular weight organic acids in calcium carbonate crystallization in the absent and present of Li + for considering the strong stabilizing effects of Li + on the {001} faces of calcite. [ 18 ] Five typical OAs of lactic acid (LA, CH 3 CH(OH)COOH, 1 alcoholic ─OH group and 1 carboxyl group), malic acid (MA, HOOCCH(OH)CH 2 COOH, 1 alcoholic ─OH group and 2 carboxyl groups), citric acid (CA, HOOCCH 2 C(OH)COOHCH 2 COOH, 1 alcoholic─OH group, and 3 carboxyl groups), succinic acid (SA, HOOCCH 2 CH 2 COOH, 0 alcoholic ─OH group and 2 carboxyl groups) and tartaric acid (TA, HOOCCHOHCHOHCOOH, 2 alcoholic ─OH groups and 2 carboxyl groups) derived from geological and biological mineralization were selected to study the regulatory effects of low molecular weight organic acids on calcite morphologies under mild conditions. The biomineralization ideas to synthesize calcite can not only help us understand the crucial role of alcoholic ─OH groups and carboxy groups of biomolecules in the regulation of calcite crystallization, but also help the clean synthesis of calcite to meet various chemical industry needs.…”
Section: Introductionmentioning
confidence: 99%
“…Calcite crystals growing on mica continuously change their crystal habit from typical rhombohedra bounded by {104} planes to flat tabular plates exposing the (001) face. As the (001) plane of calcite is dipolar, composed of a sublayer of Ca or CO 3 , it is usually unstable in the absence of adsorbed species such as Li + ions 81,82 or organic additives. 83 In our experiments, calcite crystals can express (001) planes due to the combined effect of the oriented growth on mica and the spatial confinement of SFA.…”
Section: ■ Discussionmentioning
confidence: 99%